15 UMPSA students explore culture, technology, and life of the Islamic community in Japan - Muhammad Aizat, Azed (UMPSA, 2024)
ASAKUSA, JAPAN, 7 October 2024 – A total of 15 Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) students participated in various engaging activities in Japan through the Electro-Explore@Japan international mobility programme from 1 to 7 October 2024.